Evaluation of Protein Content, Moisture Content, and Sensorial Acceptability of Crackers with the Addition of Moringa Leaf Puree - Kristianus Elky Saputra Ladiba; Nelsy Dian Permatasari; Jatmiko Eko Witoyo (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
Crackers are a popular traditional Indonesian snack that generally has a low protein content. Fortification with natural ingredients rich in nutrients, such as Moringa leaves puree, is an alternative to increase the nutritional value of crackers. Nevertheless, the utilization of moringa leaves in food systems, particularly in Kalimantan Barat, remains relatively underdeveloped. So, this study aims to evaluate the protein content, moisture content, and sensory acceptance of crackers with various additions of moringa leaf puree. Crackers were made by adding moringa leaf puree at concentrations of 0% (control), 3%, 5%, and 7% (w/w). Protein content was analyzed using the Kjeldahl method, and moisture content was analyzed using the thermogravimetric method. Sensory acceptability, including color, aroma, taste, and texture, was evaluated using a scoring test, and overall acceptability was assessed using a hedonic test with 20 semi-trained panelists. Data analysis for protein and moisture content employed linear regression, while sensory acceptability was evaluated using One-way ANOVA. Results indicated that the addition of Moringa leaf puree tends to increase the protein and moisture content of the uncooked raw crackers, achieving R² values of 0.9715 and 0.9018, respectively, as determined by linear regression analysis. The scoring test revealed that the addition of moringa leaf puree significantly influenced all observed attributes. According to hedonic testing, crackers containing 5% moringa leaf puree were the most preferred by-panelists. This study concludes that a concentration of 5% moringa leaf puree is the recommended formula for producing crackers with enough nutritional value and favorable sensory acceptance by panelists. Keywords: crackers, moisture content, Moringa leaves puree, protein content, sensorial acceptability